2013
DOI: 10.1016/j.apergo.2012.04.013
|View full text |Cite
|
Sign up to set email alerts
|

The role of VGI and PGI in supporting outdoor activities

Abstract: This paper explored the question of how volunteered and professional geographic information (VGI and PGI) can be used together in an outdoor recreation context. In particular, consideration is given to what makes each information source valuable to the user, and how this can be used to help developers of GIS provide more useful, usable and satisfying products. The assumption that VGI is inferior to PGI is shown to be unfounded; rather each has its own strengths in describing particular aspects of the user info… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 22 publications
0
9
0
3
Order By: Relevance
“…Other studies that focused on the applicability of VGI also revealed the potential of OSM during disaster relief efforts [31] or when deciding whether VGI or professional geographic information (PGI) serve as a better data source when planning outdoor activities [32]. The importance of VGI and PGI data sources for map design purposes and users' perception of information was also investigated in more detail [33,34].…”
Section: Contribution Patterns In Osmmentioning
confidence: 99%
“…Other studies that focused on the applicability of VGI also revealed the potential of OSM during disaster relief efforts [31] or when deciding whether VGI or professional geographic information (PGI) serve as a better data source when planning outdoor activities [32]. The importance of VGI and PGI data sources for map design purposes and users' perception of information was also investigated in more detail [33,34].…”
Section: Contribution Patterns In Osmmentioning
confidence: 99%
“…Although authors such as Flanagin and Metzger (2008) have highlighted concerns with the quality and reliability of volunteered information, others -e.g. Parker et al (2013) -have shown that volunteered information is used widely within certain contexts, and is typically integrated with other professional information in order to 'converge on a Table 3 Attitudes towards public transport.…”
Section: Qualitative Analysismentioning
confidence: 99%
“…Credibility has also been shown to be one of the key factors in a person's decision to use or not use a source of geographic information (Keßler, Trame, and Kauppinen 2011;Bishr and Janowicz 2010). Additionally, Parker, May, and Mitchell (2012a) highlighted how factors that contribute to trust are a critical factor in the user's evaluation of information originating from volunteers. Several authors (Fogg and Tseng 1999;Flanagin and Metzger 2008;Fogg et al 2001) have discussed the definitions, complex relationships and ambiguities associated with terms such as 'trust', 'credibility' and 'quality'.…”
Section: Measurement Of Trust In Online Map Mashup Judgementsmentioning
confidence: 99%
“…Therefore, both null and alternative hypothesised were constructed (see Table 2). As previous work on the influence of VGI and PGI on users may be considered somewhat contradictory, with both positive (Haklay 2010;Parker, May, and Mitchell 2012a) and negative (Flanagin and Metzger 2008;Jackson et al 2013) effects recorded, a two-tailed hypothesis was used.…”
Section: Hypothesesmentioning
confidence: 99%